2017
DOI: 10.5709/ce.1897-9254.227
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Conditioning of Job Satisfaction. A Model of Job Satisfaction

Abstract: This work is licensed under a Creative Commons Attribution 4.0 International License. Job satisfaction is an important predictor of job switching. Knowledge of the predictors of job satisfaction offers business owners and management staff the ability to shape the work environment so that the most valuable, loyal, and experienced employees can be retained in the company. The objective of this project is to test a model of job satisfaction based on person-organization fit (P-O fit), perceived organizational supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
(56 reference statements)
0
15
0
7
Order By: Relevance
“…This can be interpreted as a feeling due to the fulfillment of his need and desire (Arianti et al, 2020). An individual experiences a good treatment from supervisor and he will be satisfied (Wnuk, 2017). Referring to Akdol & Arikboga (2017) research, it found that LMX has positive effects to job satisfaction.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…This can be interpreted as a feeling due to the fulfillment of his need and desire (Arianti et al, 2020). An individual experiences a good treatment from supervisor and he will be satisfied (Wnuk, 2017). Referring to Akdol & Arikboga (2017) research, it found that LMX has positive effects to job satisfaction.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…Kepuasan kerja dapat dipengaruhi dari dua faktor yaitu faktor individu antara lain karakteristik kepribadian, gender, usia dan kesesuaian individu dengan pekerjaan (Spector, 1997), serta dari faktor organisasi antara lain organizational identification (Alegre, Mas-Machuca, & Berbegal-Mirabent, 2016), working environment (Raziq & Maulabakhsh, 2015), leadership style (Tepret & Tuna, 2015), job crafting (Cheng & O-Yang, 2018), persepsi dukungan organisasi (Wnuk, 2017), keadilan organisasi (Zainalipour, Fini & Mirkamali, 2010).…”
Section: Pendahuluanunclassified
“…Menurut Spector (1997), kepuasan kerja merupakan evaluasi positif atau negatif yang dilakukan individu mengenai pekerjaannya baik secara keseluruhan maupun hanya aspek pekerjaannya, dimana aspek-aspek pekerjaan yang dimaksud meliputi gaji, promosi, supervisi, tunjangan tidak langsung, penghargaan atas kinerja dan prestasi, kondisi kerja, sifat pekerjaan, rekan kerja dan komunikasi dalam organisasi, sehingga dari hasil evaluasi ini mempengaruhi perilaku karyawan dalam perusahaan (Spector, 1997). Kepuasan kerja dapat dipengaruhi dari dua faktor yaitu faktor individu antara lain karakteristik kepribadian, gender, usia dan kesesuaian individu dengan pekerjaan (Spector, 1997), serta dari faktor organisasi antara lain organizational identification (Alegre, Mas-Machuca, & Berbegal-Mirabent, 2016), working environment (Raziq & Maulabakhsh, 2015), leadership style (Tepret & Tuna, 2015), job crafting (Cheng & O-Yang, 2018), persepsi dukungan organisasi (Wnuk, 2017), keadilan organisasi (Zainalipour, Fini & Mirkamali, 2010). Dalam mewujudkan keberhasilan perusahaan meningkatkan kepuasan kerja karyawan, salah satunya berkaitan dengan faktor organisasi yaitu perilaku organisasi untuk berlaku adil dalam proses operasional dan proses pengambilan keputusan yang memengaruhi kesejahteraan serta keadilan bagi karyawan dalam menunjang tercapainya keberhasilan perusahaan (Sari, 2019).…”
Section: Pendahuluanunclassified